MENINGKATKAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN MELALUI BERMAIN PERAN - Sutinah; Arri Handayani; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Early childhood is a child in the age range of 0-6 years who is in a sensitive period, namely in a condition of very rapid growth and development. Aspects of development at this age must be stimulated optimally. Our job as parents or teachers is to facilitate their growth and development. One aspect of the development of children aged 0-6 years that must be developed is social emotional development. Social development is the ability to behave according to social demands. Meanwhile, emotional development is a complex condition that can take the form of feelings or mental vibrations which are characterized by biological changes that appear to accompany a behavior. Children's emotional development is a form of communication so that children can express all their needs and feelings to other people. Emotional development can also influence a child's personality and adjustment in socializing with the environment. The social emotional development of children aged 5-6 years can be stimulated through play activities. Play activities can prepare children to face learning experiences to socialize and how children learn to control emotions appropriately when socializing. One game that can stimulate the social emotional development of children aged 5-6 years is role playing.